2015
DOI: 10.2323/jgam.61.44
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction: Characterization of giant spheroplasts generated from the aerobic anoxygenic photosynthetic marine bacterium <i>Roseobacter litoralis</i>

Abstract: DNA extracted from the bacterial culture used in this paper was analyzed by the massively parallel DNA sequencing. The sequence similarity search showed that most of the obtained DNA sequences were similar to those of Enterobacter genomic DNA. PCR analyses using primers to detect Enterobacter DNA showed that the original Roseobacter culture was contaminated with this bacterium. The authors recognized that the cultures used in this paper were considered as a mixture of Enterobacter and Roseobacter litoralis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This is significant as ABC-type transporters are reported to play an important role in iron uptake in deep-sea hydrothermal vents (Li et al, 2014), and the Mn 2+ transporter of the VIT1/CCC1 family was reported in eukaryotic cells to be able to transport Mn 2+ into vacuoles, thereby minimizing the toxic effects of an over-accumulation of Mn 2+ in cells in a Mn-abundant environment (Tsednee et al, 2019). It is possible that the Mn 2+ transporter may also play a similar role in the hadal roseobacters since some Roseobacter cells may contain vacuole-like structures (Nojiri et al, 2015).…”
Section: Inorganic Metal Transportmentioning
confidence: 99%
“…This is significant as ABC-type transporters are reported to play an important role in iron uptake in deep-sea hydrothermal vents (Li et al, 2014), and the Mn 2+ transporter of the VIT1/CCC1 family was reported in eukaryotic cells to be able to transport Mn 2+ into vacuoles, thereby minimizing the toxic effects of an over-accumulation of Mn 2+ in cells in a Mn-abundant environment (Tsednee et al, 2019). It is possible that the Mn 2+ transporter may also play a similar role in the hadal roseobacters since some Roseobacter cells may contain vacuole-like structures (Nojiri et al, 2015).…”
Section: Inorganic Metal Transportmentioning
confidence: 99%